THE ENDS OF ISLAMIC ECONOMICS FROM THE PERSPECTIVE OF HOMO ECONOMICUS AND HOMO ISLAMICUS: A CRITICAL STUDY - Satria Hibatal Azizy (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2019)
This paper compares the ends of economic from homo economicusand homo Islamicusperspective. It is a literature study that is combined with the argumentative approach in order to provide the valid comparison of these two. The end or the goal of economics is one of important component of microfoundations of economics. It will become one deciding factor in chosing the most suitable economic agent for Islamic economics. The result of this study shows that the end of economics from homo economicusperspective, which is maximization of utility, is facing a huge criticism. The same case is shown in the end of economics from homo Islamicusperspective, which is maximization of maslahah. This paper later suggests the use of incremental welfare value as the end of economics.